Infectious Disease Informatics - Sintchenko, Vitali (Springer New York : Imprint: Springer, 2010)
In this book, Vitali Sintchenko brings together a collection of state-of-the-art reviews of informatics applications aiming to improve the diagnosis, prevention, treatment and control of infectious diseases. In response to the need for computational biology techniques geared towards clinical medicine, this volume covers the emerging domains of translational bioinformatics, genomics enabled decision support, intelligent design of vaccines and antimicrobial drugs as well as new types of biosurveillance. This book is written by a diverse, international group of experts in the field and provides clinicians, pathologists, biomedical researchers and informaticians with an essential resource that offers also a fascinating glimpse into the future of this dynamic field. Vitali Sintchenko (MBBS, PhD, FRCPA, FACHI) is a clinical microbiologist and informatician with the Sydney Medical School, The University of Sydney, Australia.